2017
DOI: 10.3390/polym9070294
|View full text |Cite
|
Sign up to set email alerts
|

Gas Barrier, Thermal, Mechanical and Rheological Properties of Highly Aligned Graphene-LDPE Nanocomposites

Abstract: This contribution reports on properties of low-density polyethylene-based composites filled with different amounts of graphene nanoplatelets. The studied samples were prepared in the form of films by means of the precoating technique and single screw melt-extrusion, which yields a highly ordered arrangement of graphene flakes and results in a strong anisotropy of composites morphology. The performed tests of gas permeability reveal a drastic decrease of this property with increasing filler content. A clear cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 56 publications
(72 reference statements)
4
72
0
Order By: Relevance
“…The nanoplatelets are aligned along the extrusion flow direction. This effect was also observed in our earlier study [3,5]. The difference in size between fillers is visible, however some agglomerates are present in both samples.…”
Section: Morphologysupporting
confidence: 88%
See 1 more Smart Citation
“…The nanoplatelets are aligned along the extrusion flow direction. This effect was also observed in our earlier study [3,5]. The difference in size between fillers is visible, however some agglomerates are present in both samples.…”
Section: Morphologysupporting
confidence: 88%
“…Properties of the nanoplatelets and molecular weight parameters of the LDPE, measured by means of Gel Permeation Chromatography and DSC, are presented in Gaska et al [3,5] Graphene nanopletelets were dispersed into acetone and stirred by high shear rotor stator mixer for 20 minutes at 10 000 rpm, then sonicated for 3h, 90W. Thereafter graphene-acetone suspension was mixed with LDPE in the powder form for 1h at 500 rpm using overhead stirrer until total solvent evaporation.…”
Section: Methodsmentioning
confidence: 99%
“…Pierleoni et al also investigated filtered papers of GNPs and reported that even at graphene loadings as low as 0.4 wt%, a 74% depreciation in oxygen permeability could be achieved. An alternative route to improve the fluid barrier performance of thermoplastic polymers is through incorporation of GNPs via melt processing . Gaska et al achieved improvements in barrier performance of low‐density polyethylene (LDPE) to CO 2 and SF 6 of 65.5 and 80.5%, respectively, for LDPE loaded with 7.5 wt% GNP.…”
supporting
confidence: 60%
“…An alternative route to improve the fluid barrier performance of thermoplastic polymers is through incorporation of GNPs via melt processing . Gaska et al achieved improvements in barrier performance of low‐density polyethylene (LDPE) to CO 2 and SF 6 of 65.5 and 80.5%, respectively, for LDPE loaded with 7.5 wt% GNP. Checchetto et al found 5 wt% GNPs reduced LDPE permeability to H 2 , N 2 , and CO 2 by ≈40%.…”
mentioning
confidence: 99%
“…All the samples were etched for 30 h using a solution of 1% w/w potassium permanganate in a mixture of 98% of sulfuric acid, 85% of ortho-phosphoric acid and water. 37 The process was terminated by cleaning the samples in a mixture of sulfuric acid and deionized water, thereaer in hydrogen peroxide and next in deionized water.…”
Section: Surface Treatmentmentioning
confidence: 99%